Review on Risk Assessment and Risk Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Risk assessment and planning were developed some 30–40years ago as a scientific field. Principles and strategies for the conceptualization, evaluation and management of risk were developed. Such principles and techniques still constitute the cornerstone of this field today to a large extent, but many developments have been made, connected with both the theoretical basis and functional models and procedures. The risk management study began after World War II. Risk management has long been linked to the use of market insurance to protect individuals and businesses from various accident-related losses. Many types of risk management, alternatives to traditional insurance, emerged during the 1950s when market insurance was considered to be very expensive and inadequate for mere risk protection. During the 1970s, the use of derivatives as risk management tools emerged and expanded rapidly during the 1980s, as companies increased their financial risk management. Global risk control started in the 1980s and internal risk management models and capital measurement formulas were developed by financial firms to protect against unanticipated threats and minimize regulatory resources.